THE CENTRAL CAUCASO-ASIAN COUNTRIES AND THE PROSPECTS OF ACCESSION TO THE EURASIAN ECONOMIC UNION - PAPAVA, Vladimer (CENTRAL ASIA AND THE CAUCASUS, 2019)
This article considers the possible enlargement of the Eurasian Economic Union (EAEU) through the accession of post-Soviet countries that form the geopolitical region of Central Caucaso-Asia. Three countries of that region—Armenia, Kazakhstan, and Kyrgyzstan—are already members of the EAEU. The possible accession of the other Central Caucaso-Asian countries—Azerbaijan, Georgia, Tajikistan, Turkmenistan, and Uzbekistan—remains an open question. In search of an answer, the author analyzes the main features of Central Caucaso-Asia as a region and examines the basic economic mechanism of EAEU integration, which is based on a redistribution of customs revenue from the export of Russia’s hydrocarbon resources in favor of the other Union countries. The sanctions against Russia imposed by the United States and other countries, as well as the counter-sanctions imposed by Moscow in response to them, significantly complicate the functioning of the EAEU as a regional economic association, thus considerably reducing its attractiveness to countries that can be regarded as potential members of this Union in the foreseeable future. At the same time, for Central Caucaso-Asian countries that have hydrocarbon resources of their own (Azerbaijan, Turkmenistan, and Uzbekistan), the economic mechanism for redistributing customs revenue from Russian hydrocarbon exports at work in the EAEU may prove to be entirely insufficient to induce them to join the Union. The remaining countries of Central Caucaso-Asia (Georgia and Tajikistan) differ markedly in their attitude toward possible EAEU membership. For Georgia, its European orientation is a matter of principle. Today, it is underpinned by the EU-Georgia Association Agreement (signed in 2014 and effective since 2016), which includes, as an integral part, an agreement establishing a Deep and Comprehensive Free Trade Area (DCFTA). For Tajikistan, there are no fundamental obstacles to possible EAEU membership, although Western sanctions against Russia and Russian counter-sanctions, all other things being equal, may be seen by Dushanbe as something of a barrier to EAEU accession. At the same time, of all the Central Caucaso-Asian countries that are not members of the EAEU, Tajikistan is the most likely one to join the Union.